2017
DOI: 10.1530/erc-17-0121
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for the development of alternative forms of androgen deprivation therapy

Abstract: With few exceptions, the almost 30,000 prostate cancer deaths annually in the United States are due to failure of androgen deprivation therapy. Androgen deprivation therapy prevents ligand-activation of the androgen receptor. Despite initial remission after androgen deprivation therapy, prostate cancer almost invariably progresses while continuing to rely on androgen receptor action. Androgen receptor's transcriptional output, which ultimately controls prostate cancer behavior, is an alternative therapeutic ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 155 publications
(217 reference statements)
0
20
0
Order By: Relevance
“…Nonetheless, the presence of canonical AREs, usually defined as 15 bp full-length sequence, ranged from about 2.5% to 54% among studies [ [34] , [35] , [36] , [37] , [38] , [39] ]. These studies suggested also that AR binding to AREs allows for one to three bases degeneration in the consensus ARE motif, differences in orientation of the hexamer half sites, more variable spacing between these half sites, or in some cases just one ARE half site/hexamer, the latter possibly in combination with recognition motifs for other transcription factors such as FoxA1 [ 12 ]. In addition to liberty in the specific sequence of DNA motif to which AR binds, it is now clear that the scope and composition of the AR cistrome, i.e.…”
Section: Key Determinants Of Ar Transcriptional Activitymentioning
confidence: 99%
See 4 more Smart Citations
“…Nonetheless, the presence of canonical AREs, usually defined as 15 bp full-length sequence, ranged from about 2.5% to 54% among studies [ [34] , [35] , [36] , [37] , [38] , [39] ]. These studies suggested also that AR binding to AREs allows for one to three bases degeneration in the consensus ARE motif, differences in orientation of the hexamer half sites, more variable spacing between these half sites, or in some cases just one ARE half site/hexamer, the latter possibly in combination with recognition motifs for other transcription factors such as FoxA1 [ 12 ]. In addition to liberty in the specific sequence of DNA motif to which AR binds, it is now clear that the scope and composition of the AR cistrome, i.e.…”
Section: Key Determinants Of Ar Transcriptional Activitymentioning
confidence: 99%
“…Like many transcription factors, AR relies on functional and structural interactions with other transcriptional regulators to ensure proper transcription of its target genes [ 12 , 15 ]. Some of these AR-associated proteins clearly display the characteristics of a coregulator, i.e.…”
Section: Key Determinants Of Ar Transcriptional Activitymentioning
confidence: 99%
See 3 more Smart Citations